2022
DOI: 10.1186/s12884-022-04720-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, marginalisation and disempowerment – understanding how interactions with health providers can influence smoking cessation in pregnancy

Abstract: Background Maternal smoking during pregnancy can lead to serious adverse health outcomes for both women and their infants. While smoking in pregnancy has declined over time, it remains consistently higher in women with lower socioeconomic circumstances. Furthermore, fewer women in this group will successfully quit during pregnancy. Aim This study explores the barriers to smoking cessation experienced by socially disadvantaged pregnant women and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Several studies indicate that concern about the effects of smoking on their baby’s health and the desire to quit smoking to protect their unborn child may serve as facilitators to help pregnant women quit smoking 43 , 44 . However, some pregnant mothers report being unclear about whether smoking is truly harmful to their babies 45 , 46 . Although there is little research related to prenatal TSE and long-term neurodevelopmental outcomes in children who were born preterm, one study of preterm infants born at < 32 weeks GA found poor motor and cognitive outcomes at 2 years corrected age in those who were exposed to prenatal TSE compared to those with no prenatal TSE 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that concern about the effects of smoking on their baby’s health and the desire to quit smoking to protect their unborn child may serve as facilitators to help pregnant women quit smoking 43 , 44 . However, some pregnant mothers report being unclear about whether smoking is truly harmful to their babies 45 , 46 . Although there is little research related to prenatal TSE and long-term neurodevelopmental outcomes in children who were born preterm, one study of preterm infants born at < 32 weeks GA found poor motor and cognitive outcomes at 2 years corrected age in those who were exposed to prenatal TSE compared to those with no prenatal TSE 47 .…”
Section: Discussionmentioning
confidence: 99%
“…NRT are recommended and endorsed as part of standard practice in the UK. However, pregnant women have identified the need for greater options and support for smoking cessation strategies [11]. Rates of smoking in pregnancy are also higher among people with more socioeconomic disadvantage [12], yet evidence suggests that women from lower socioeconomic backgrounds might benefit less from interventions currently available [13].…”
Section: Introductionmentioning
confidence: 99%